Sistem Pendidikan Ganda dan Diagnostic Trouble Box (DTB) dalam Pembelajaran di Intercompany Training Mercedez Kraftfahrzeuggewerbe Saarländischer KFZ-Verband Trainingszentrum–Saarbrücken Germany - Ridho Saputro (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
The sending of 1200 educators and education staff abroad in 2019 is one of the government's efforts to improve teacher competencies to strengthen education in Indonesia so that it is more developed and equal with developed countries in the world. The purpose of the country which I will present this time is the German state, at the Intercompany Trainning Mercedez Kraftfahrzeuggewerbe Saarländischer KFZ-Verband Trainingszentrum - Saarbrücken Germany. What is very interesting about the German state is the very close relationship between the industrial world and the world of education, where Germany was the first country to initiate a dual system education system (Dual System Education). Teaching methods use the Diagnostic Trouble Box as used in Germany, as one of the interesting methods and media and can find out students' analytical skills easily and accurately, especially in learning electrical vehicle automotive.